RETROSPECTIVE ANALYSIS OF THE PARASITIC CONTAMINATION OF SOIL SAMPLED IN THE ASTRAKHAN REGION IN 2011-2015 - T.V. NIKESHINA; R.S. ARAKELYAN; N.Z. SALIKHOV; A.I. BOLDYREVA (Avicenna Tajik State Medical University, 2021)
Objective: To study and analyze the parasitic contamination of soil in the Astrakhan region in 2011-2015. Methods: On the territory of the Astrakhan region from 2011 to 2015, specialists at the Center for Hygiene and Epidemiology in the Astrakhan region examined 4873 soil samples for parasitic contamination. Results: Out 4873 samples investigated, 7.4% (361 samples) did not meet hygienic standards in terms of parasitological indicators. Most of the soil samples were taken from the residential area - 78.7% (3835 samples). The positive samples at the site turned out to be 7.4% (285 samples); these samples were contaminated with helminths and protozoa. Almost 7.5 times fewer samples were taken from other areas (health care facilities, private yards, beaches, public utility facilities); they accounted for 10.3% (501 samples), of which 2.8% proved to be positive (14 samples). The share of soil samples taken from industrial zones and transportation linkages areas was 6.8% (330 samples), where eggs and larvae of helminths were found in the samples studied. In isolated and rare cases, studies were carried out on soil samples taken from crop production areas - 1.5% (75 samples), of which Toxocara eggs were found in 13.3% (10 samples). The share of soil samples taken from the areas of livestock complexes and farms was 1.97% (96 samples), including 12.5% being positive, as larvae of Strongyles were found. The studied soil samples taken from the areas of childcare facilities and playgrounds accounted for 85% (3259 samples). The number of positive samples at these facilities was 6.5% (213 samples), in which both helminths and protozoa were found. The share of soil samples taken in the water supply areas was 0.5% (23 samples) - all studied samples' results complied with accepted standards. Of the 13 soil samples taken from various resort premises, positive results amounted to 15.4% (2 samples). Conclusion: High-level parasitic contamination of the soil has continued to persist for a number of years. The most significant number of positive results was noted in 2011 and amounted to 8.9%. Most often, areas of childcare facilities were contaminated with helminths and protozoa. The presence of helminthic-protozoal parasites points to contamination of these locations with the feces of infected animals and/or people.